Waqf-Based Forests: A Sustainable Solution for Agromaritime Development through Islamic Social Finance - Khalifah Muhamad Ali; Miftahul Jannah; Mu'minah Mustaqimah; Romzie Rosman (Department of Islamic Economics, IPB University, 2026)
Deforestation remains a critical issue globally, significantly impacting Indonesia's agromaritime regions. This study explores the innovative concept of waqf-based forests as a sustainable solution for forest conservation and agromaritime development through Islamic social finance. Despite increasing research, a comprehensive analysis of their potential remains limited. This research addresses this gap by drawing on Islamic literature, Indonesian regulations, in-depth interviews, and observing several waqf-based forest practices in Indonesia. Using a descriptive analysis approach, the study finds that waqf-based forests, established on waqf land, serve as a unique form of land waqf for forest preservation and sustainable land use in agromaritime areas. This concept, with historical roots in the Utsmaniyyah Caliphate, aligns with Islamic principles and Indonesian laws that protect waqf assets. Currently, waqf-based forests are expanding across Indonesian provinces, presenting a model for sustainable forest and agromaritime development. This practice integrates religious, social, and financial instruments, positioning Waqf as a vital contributor to forest preservation and agromaritime sustainability. The study advocates for promoting waqf-based forests as a comprehensive solution to deforestation and a catalyst for agromaritime development, urging active engagement from government bodies, companies, and communities to support this sustainable conservation effort through Islamic social finance.